DEVELOPMENT OF CLINICAL LEGAL STUDIES AS AN ESSENTIAL COMPONENT IN THE MODERNIZATION OF LEGAL EDUCATION - Tatyana V. Khudoykina; Vladlena V. Lysenko (National Research Mordova State University, 2017)
Introduction: the current modernization of legal education in Russia puts emphasis upon the development of its practical component. Enhancement of the quality of higher legal education directly depends on the inclusion of practice-oriented components. In this respect, it is necessary to develop training of future lawyers based on legal clinics as structural units of higher educational institutions. Clinical legal education should combine the special pre-theoretical training of students as well as the practical work that has to do with rendering free legal assistance to socially vulnerable categories of citizens. Materials and Methods: comparative analysis of the experience of various Russian legal clinics made it possible to identify the similarities and differences between them, comparing different versions of clinical training, recognizing common problems and proposing an effective model of legal clinics' activity enabling the learners to obtain professional skills and to improve the quality of legal services rendered by students. Results: the authors demonstrate and analyze different activities of Russian legal clinics, established in institutions of higher education. The process of detecting differences among structural divisions of universities providing legal training, allowed us to determine the common problems encountered by a legal clinic during day-to-day activity. The authors propose a model for legal clinics' effective activity pertaining to the implementation of a practice-based training of students. The article reveals the learning process of developing professional skills (interviewing and advising on legal issues, drafting legal documents, case analysis, etc.) gradually. Necessary conditions for ensuring quality of legal services provided by students under the guidance of teachers are highlighted. Discussion and Conclusions: recommendations for the future development of legal clinic education in Russian universities are given. The importance of expanding legal clinic-based education, its implementation in the educational process is underscored. The significance of legal clinics for bachelor's and master's degree programmes is pointed.